ANALISIS PENGUKURAN SUHU TUBUH BAYI BALITA DENGAN BERBAGAI JENIS TERMOMETER - Vivian Nanny Lia Dewi; Dechoni Rachmawati (Medika Respati : Jurnal Ilmiah Kesehatan, 2016)
ANALISIS PENGUKURAN SUHU TUBUH BAYI BALITA DENGAN BERBAGAI JENIS TERMOMETER Vivian Nanny Lia Dewi1*, Dechoni Rachmawati1  1Stikes Jenderal A Yani Yogyakarta,Jl. Ring Road Barat Ambarketawang, Gamping Sleman, Yogyakarta, 55294, IndonesiaSurat Menyurat umivivian@gmail.comAbstractRasionale: Nearly 10 million children die annually before the age of 5 years. In general, mortality in infants and toddlers due to the five conditions that can be prevented and treated pneumonia, diarrhea, malaria, measles, and malnutrition. Child's responses to these different conditions, one of which is a fever, therefore, inspection and monitoring of temperature is one important indicator in assessing the health condition of the child's fever. Although the temperature probe is not painful, but in general, children showed reactions of anxiety and excessive stress at the time of the examination body temperature for a long time. However, there is still controversy regarding the most appropriate thermometer and the best place for temperature measurement as well as comfortable for the baby toddlersPurpose: To determine the sensitivity and specificity of the various types of thermometer in measuring fever in baby and toddlersMethod: Descriptive analytic research. Sample were infants and toddlers aged 0-5 years who have a fever of 25 people and normal temperature of 25 people. Accidental sampling technique. The experiment was conducted in July-September 2016 held at PKU Muhammadiyah Gamping, Sleman, Yogyakarta Hospital. Data analysis using sensitivity and specificity test (area under curve)Result: Area under the curve of the most widely away is thermometer oral digital (0978), followed by axillary mercury thermometer for 5 minutes (0958), axillary mercury thermometer 3 minutes (0942), tympanic thermometer (0927), Digital axillary thermometer (0924), and forehead thermometer (0.900).Conclusion: The highest results of sensitivity and specificity is digital oral thermometer. Key words: Thermometer, temperature, baby-toddler